The art of mental maps in reading comprehension in students of the faculty of education of the university of the amazon intercultural, Yarinacocha – 2012 - Santacruz-Espinoza, Atanacia (2019)
This study is part of the line of methodological strategies, the general problem is: To what extent the application of the technique of mental maps inuence the reading comprehension in Cycle II students of the Faculty of Education at the University National Intercultural Amazon, Yarinacocha - 2012? The overall objective is: Determine the inuence of the application of the technique of Mind Mapping on Reading Comprehension in Cycle II students of the Faculty of Education at the National Intercultural University of Amazonia , Yarinacocha - 2013 The application of mind mapping technique signicantly inuence reading comprehension in Cycle II students of the Faculty of Education at the National Intercultural University ofAmazonia, Yarinacocha - 2012 research falls within the type of applied research, explanatory level, quasi experimental. The population consisted of 453 students from the Faculty of Education and the sample was not random and consisted of 50 students of the second cycle of the Faculty of Education. It is concluded that the application of the technique of mind mapping signicantly inuence reading comprehension in Cycle II students of the Faculty of Education at the National Intercultural University of Amazonia , Yarinacocha - 2013, with a signicance level of 5% and t is greater than 5% (27,855 > 2.05).